A quinol oxidase, encoded by cyoABCD, is utilized to adapt to lower O(2) concentrations in Rhizobium etli CFN42 - Lunak, Zachary R. (Microbiology (Reading), 2015)
Bacteria have branched aerobic respiratory chains that terminate at different terminal oxidases. These terminal oxidases have varying properties such as their affinity for oxygen, transcriptional regulation and proton pumping ability. The focus of this study was a quinol oxidase encoded by cyoABCD. Although this oxidase (Cyo) is widespread among bacteria, not much is known about its role in the cell, particularly in bacteria that contain both cytochrome c oxidases and quinol oxidases. Using Rhizobium etli CFN42 as a model organism, a cyo mutant was analysed for its ability to grow in batch cultures at high (21 % O(2)) and low (1 and 0.1 % O(2)) ambient oxygen concentrations. In comparison with other oxidase mutants, the cyo mutant had a significantly longer lag phase under low-oxygen conditions. Using a cyo :: lacZ transcriptional fusion, it was shown that cyo expression in the wild type peaks between 1 and 2.5 % O(2). In addition, it was shown with quantitative reverse transcriptase PCR that cyoB is upregulated approximately fivefold in 1 % O(2) compared with fully aerobic (21 % O(2)) conditions. Analysis of the cyo mutant during symbiosis with Phaseolous vulgaris indicated that Cyo is utilized during early development of the symbiosis. Although it is commonly thought that Cyo is utilized only at higher oxygen concentrations, the results from this study indicate that Cyo is important for adaptation to and sustained growth under low oxygen.